Efeitos subjetivos do uso de alcool em adolescentes de Cabinda, Angola - Domingos Sebastiao Luemba Sambo (2015)
This study is confined to the region of Cabinda, one of the 18 provinces of Angola (Africa), where there are various social problems, among which, teenagers significant use of alcohol. Researches carried out by Cabinda graduates in their final dissertations do not show any data related to our research, neither do the Centers for African Studies of universities of Africa, South America, Europe and other regions. For this reason, we wanted to know the subjective effects that alcohol has on teenagers psychic constitution and the role of the school in the teenagers consciousness raising and in their education against alcohol consumption. We analyzed academic, journalistic, statistic, governmental and non-governmental sources of Angola which explain this phenomenon insufficiently. To show the evidence of this research, we conducted a preliminary and statistic survey on Comandante Gikas Schools teenagers about their personal, social, and school conditions as well as about alcohol and its consumption. We also analyzed possible school programs that dealt with this theme and which explained its effects. This enabled us to know some of these teenagers, aged between 12 and 18, used to consuming alcohol, and who turned out to be the subjects of our research. For its continuity we reviewed the literature and the theoretical foundation, including the notion about teenagers constitution as a basis in developmental and contemporary psychoanalysis. We also conducted a field survey, focal group and in-depth interviews guided by the psychoanalytic clinic method. Results reveal that there is an upsetting situation regarding teenagers, and this situation has various forms of manifestations, including the use of legal and illegal substances the effects of which are robbery, physical, psychological and moral aggressions against people, hyper sexuality, provocations, break-ins, and other crimes. Such effects display the conflict or the split between the name of the State (norms, laws and juridical impositions), the name of the family (cultural, traditional, and family habits), and the name of the Group (media, Staffs, and peers). All of them are three forms of identification of different instances which can be bringing confusion to the youth of Cabinda.